2012
DOI: 10.1002/pola.26362
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene glycol‐based ionic liquids via azide/alkyne click chemistry

Abstract: A facile synthetic route for the preparation of dicationic ethylene glycol based-ionic liquids (ILs) via the azide/ alkyne ''click'' reaction is presented. The copper(I) catalyzed, microwave-assisted azide/alkyne ''click'' reaction between diazido-ethylene glycols and the corresponding alkyne containing IL-head group enables a simple preparation of different sets of poly(ethylene glycol)-based ILs. Beside tetra-and hexa(ethylene glycol)-based ILs, also oligomeric (M n ¼ 400 g/mol) and polymeric ILs (M n up to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 62 publications
1
20
0
Order By: Relevance
“…The same behavior was observed in a previous research on the thermal stability of DIL derived from imidazolium and pyrrolidinium where the number of monomer units was n ¼5, 8, 33 [30].…”
Section: Thermal Propertiessupporting
confidence: 77%
“…The same behavior was observed in a previous research on the thermal stability of DIL derived from imidazolium and pyrrolidinium where the number of monomer units was n ¼5, 8, 33 [30].…”
Section: Thermal Propertiessupporting
confidence: 77%
“…Moreover, the values of T g reported by Binder and co-workers [49] for dicationic ILs also depended on the PEG size, as well as on the chemical nature of both the counteranion and cationic group. [49,51,59] …”
Section: Glass-transition Temperaturementioning
confidence: 92%
“…Dicationic geminal imidazolium IL with a poly(ethylene glycol) (PEG500) bridging chain and a bis(trifluoromethanesulfonyl)imide anion was synthesized and kindly provided by Dr. M. Mahrova [46,55]. The structures of the dicationic IL (IL2-di) and its monocationic analogue (IL2), which was used as a benchmark in this study, are shown in Figure 1.…”
Section: Methodsmentioning
confidence: 99%